Filing Systems in Polish SME Sector and Information Gaps Reported by Entrepreneurs - Jaworski, Jacek (Systemy ewidencyjne w polskim sektorze MŚP a luki informacyjne zgłaszane przez przedsiębiorców, 2011)
The main goal of the paper is to analyze the impact of provided filing systems on information gaps reported by the Polish small and medium enterprises. In the first part of the paper, various filing systems with their information capacity are characterized. The second part presents the results of a questionnaire survey with the statistical analysis of information gaps reported by entrepreneurs, which hinder short- and long-term decision-making.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 633-642
Keywords: information gaps; SME sector; filing systems